Determinantes de lucratividade de empresas apoiadas pelo Programa BNDES de Desenvolvimento da Indústria de Software - BNDES PROSOFT Empresa - Paiva, Elisa Junqueira de Andrade (2015)
This paper seeks to examine elements that have impact in the profitability of companies who have benefited with BNDES’ program focused on developing Brazilian’s software and IT services industry. The analysis of profitability pervades a number of studies in Brazil and abroad and is of utmost importance for constructing effective public policies. The criteria for the evaluation included different microeconomic aspects, like accounting information, employment, companies’ location and operating segment, among others, using panel data method. Among the results obtained, one can highlight the positive impact of employee's school background, former year’s profitability, the greater return of smaller firms when compared to bigger ones. Companies focused on hardware showed lower profitability, as did the ones with more employees. Evidence also suggested that signing a financing contract with the Brazilian Development Bank (BNDES) decreased companies’ profits, which were later benefited, as of implementing the project.